Optimalisasi Pelayanan 5 Meja di Posyandu Melalui Pelatihan Kader Kesehatan Untuk Mendukung Skrining Stunting - Hikmah, Faiqatul; Amareta, Dahlia Indah; Yulianti, Adhiningsih; Warsito, Heri (Indonesian Journal Publisher, 2024)
Posyandu is the most accessible place for health services for the community. The service system at Posyandu has the concept of 5 table Posyandu services. This community service activity aims to optimize the 5-desk service at Posyandu through training of health cadres to support stunting screening. This activity was attended by 25 health cadres. The material provided in this counseling is the Service System at Posyandu using table 5 system: table 1: Registration, table 2: Weighing, table 3: Filling in KMS, table 4: Individual counseling based on KMS, table 5: Family planning and health services. Extension and training activities must be carried out continuously, so that health cadres can increase their knowledge and skills. By increasing the knowledge and skills of cadres, it will certainly improve the quality of services at Posyandu.